Nigerian Water Resources Management – An Overview - Ibrahim, U. A.; Alkali, A. N.; Sanyaolu, B. O.; Usman, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Effective management of a country’s water resources contributes toward its sustainable development. The aim of this paper is to give an overview of Nigeria’s surface and underground water sources alongside agencies charged with functions covering all facets in water resources development and management. Nigeria consists of three broad agro-ecological zones; the northern Sudan Savannah, the Guinea Savannah and the southern rainforest spread across eight hydrological areas for the purpose of water resources management. The Federal Ministry of Water Resources is responsible for large water resources development projects and water allocation between states; comprising of sixteen (16) parastatals and agencies made up of twelve (12) River Basin Development Authorities (RBDAs), Nigeria Hydrological Services Agency (NIHSA), Nigeria Integrated Water Resources Management Commission (NIWRMC), Gurara Water Management Authority (GWMA), and the National Water Resources Institute (NWRI). The country has four river drainage systems and 264 dams. Recent studies of Nigerian water reserves (surface and groundwater sources) indicated that there are large supplies, and the country has surface and groundwater resources potentials of 267.3BCM and 51.9BCM respectively.